1993
DOI: 10.1016/0014-2999(93)90619-s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nimodipine on sciatic nerve blood flow and vasa nervorum responsiveness in the diabetic rat

Abstract: Evidence is accumulating that impairment of nerve blood flow is a key factor in the pathogenesis of diabetic neuropathy. Nimodipine, a 1,4-dihydropyridine type Ca2+ channel antagonist, has been shown to ameliorate an existing neuropathy in the streptozotocin-induced diabetic rat. In the present study the effect of diabetes mellitus itself and the effect of chronic nimodipine treatment on the sciatic nerve blood flow of streptozotocin-induced diabetic rats were investigated. Nerve blood flow was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…For the former, this agrees with previously reported measurements over a 4-h period [44]. The deficit in laser-Doppler flux with diabetes also agrees with several reports [6,8,43,[45][46][47][48]. It was further suggested that reduced blood flow in diabetic rats is only found when they are ketotic [49].…”
Section: Methodssupporting
confidence: 92%
“…For the former, this agrees with previously reported measurements over a 4-h period [44]. The deficit in laser-Doppler flux with diabetes also agrees with several reports [6,8,43,[45][46][47][48]. It was further suggested that reduced blood flow in diabetic rats is only found when they are ketotic [49].…”
Section: Methodssupporting
confidence: 92%
“…The deficit of approximately 50% in nerve laser Doppler flux in diabetic rats is consistent with results from other research groups who have either used Doppler flowmetry (Yasuda et al, 1989;Maxfield et al, 1993;Kappelle et al, 1993;Cameron et al, 1994b) or other methods Monafo et al, 1988;Cameron et al, 1991;Hotta et al, 1992) to estimate nerve perfusion in experimental diabetes. The validity of Doppler flowmetry as an index of nerve blood flow requires comment and, in the aforementioned papers (Stevens et al, 1993b;, we discussed the limitations and fidelity of the technique.…”
Section: Acute Bosentan Administrationsupporting
confidence: 87%
“…Thus, nerve ischaemia and endoneurial hypoxia have been reported in association with diabetic neuropathy in patients (see Tesfaye et al, 1994, for a recent review). The phenomenon has been modelled in diabetic rats and most studies on nerve blood flow or its indirect estimation via laser Doppler velocimetry report a reduction of about 50% in the sciatic nerves of rats with either streptozotocin-induced (Tuck et al, 1984;Monafo et al, 1988;Cameron et al, 1991;Kappelle et al, 1993;Stevens et al, 1993b) or genetic (Stevens et al, 1994) diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%